Quality of Care and Quality of Life: Convergence or Divergence? - Wadi B. Alonazi; Shane A. Thomas (SAGE Publishing, 2014)
The aim of this study was to explore the impact of quality of care (QoC) on patients' quality of life (QoL). In a cross-sectional study, two domains of QoC and the World Health Organization Quality of Life-Bref questionnaire were combined to collect data from 1,059 pre-discharge patients in four accredited hospitals (ACCHs) and four non-accredited hospitals (NACCHs) in Saudi Arabia. Health and well-being are often restricted to the characterization of sensory qualities in certain settings such as unrestricted access to healthcare, effective treatment, and social welfare. The patients admitted to tertiary health care facilities are generally able to present themselves with a holistic approach as to how they experience the impact of health policy. The statistical results indicated that patients reported a very limited correlation between QoC and QoL in both settings. The model established a positive, but ultimately weak and insignificant, association between QoC (access and effective treatment) and QoL ( r = 0.349, P = 0.000; r = 0.161, P = 0.000, respectively). Even though the two settings are theoretically different in terms of being able to conceptualize, adopt, and implement QoC, the outcomes from both settings demonstrated insignificant relationships with QoL as the results were quite similar. Though modern medicine has substantially improved QoL around the world, this paper proposes that health accreditation has a very limited impact on improving QoL. This paper raises awareness of this topic with multiple healthcare professionals who are interested in correlating QoC and QoL. Hopefully, it will stimulate further research from other professional groups that have new and different perspectives. Addressing a transitional health care system that is in the process of endorsing accreditation, investigating the experience of tertiary cases, and analyzing deviated data may limit the generalization of this study. Global interest in applying public health policy underlines the impact of such process on patients' outcomes. As QoC accreditation does not automatically produce improved QoL outcomes, the proposed study encourages further investigation of the value of health accreditation on personal and social well-being.